2017
DOI: 10.1089/jamp.2016.1301
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Tobacco Carcinogen-Induced Lung Tumorigenesis by Aerosol-Delivered Glycerol Propoxylate Triacrylate-Spermine Copolymer/Short Hairpin Rab25 RNA Complexes in Female A/J Mice

Abstract: Our results strongly confirm the tumorigenic role of Rab25 in tobacco carcinogen-induced lung cancer and hence demonstrate aerosol delivery of shRab25 as a therapeutic target for lung cancer treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Rab25 has been documented in the alternation of expression of apoptotic molecules; where Rab25 was found to reduce pro-apoptotic proteins BAX and BAK in ovarian cancer [28], and its knockdown tends to reduce anti-apoptotic molecule Bcl-2 in tobacco carcinogen-induced lung cancer [48]. Hence, it can be concluded that, the epithelial-specific protein, Rab25, boosts cancer progression by stimulating growth promoting signaling pathways and suppressing apoptotic cell death.…”
Section: Rab25mentioning
confidence: 99%
“…Rab25 has been documented in the alternation of expression of apoptotic molecules; where Rab25 was found to reduce pro-apoptotic proteins BAX and BAK in ovarian cancer [28], and its knockdown tends to reduce anti-apoptotic molecule Bcl-2 in tobacco carcinogen-induced lung cancer [48]. Hence, it can be concluded that, the epithelial-specific protein, Rab25, boosts cancer progression by stimulating growth promoting signaling pathways and suppressing apoptotic cell death.…”
Section: Rab25mentioning
confidence: 99%
“…Research shows that Rab 25 can promote the in vitro proliferation of renal cell carcinoma cells [21], hepatocellular carcinoma cells [13], and skin squamous cell carcinoma [22]. When levels of Rab 25 is reduced in lung cancer caused by tobacco carcinogen, tumor growth is reported to be restricted [23]. Conversely, ectopic expression of Rab 25 was reported to promote proliferation of breast cancer cells [24] and ovarian cancer cells [25].…”
Section: Rab 25 and Its Role In Cancer Progressionmentioning
confidence: 99%
“…Moreover, Rab25 suppressed apoptotic cell death by reducing the expression of pro-apoptotic molecules, BAX and BAK, in ovarian cancer [ 12 ]. Knockdown of Rab25 was found to reduce anti-apoptotic protein, Bcl-2, in tobacco carcinogen-induced lung cancer [ 50 ]. Taken together, activation of growth-stimulating signaling pathways and suppression of apoptotic cell death pathways mediate the effect of Rab25 on enhancing cancer progression.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of both in vitro cell growth and in vivo xenograft development were observed after knockdown of Rab25 in glioblastoma multiforme cells (U87MG) [ 21 ] and breast cancer cells (MCF7) [ 58 ]. Knockdown of Rab25 was reported to inhibit tumor growth in tobacco carcinogen-induced lung cancer model [ 50 ]. Conversely, ectopic overexpression of Rab25 was found to induce in vitro cell growth of breast cancer cells (MCF7) [ 12 , 58 ] and ovarian cancer cells (A2780, DOV13, HEY, OCC1) [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation